2014
DOI: 10.4049/jimmunol.1302586
|View full text |Cite
|
Sign up to set email alerts
|

Calcium Signaling via Orai1 Is Essential for Induction of the Nuclear Orphan Receptor Pathway To Drive Th17 Differentiation

Abstract: Orai1 is the pore subunit of Ca2+ release-activated Ca2+ (CRAC) channels that stimulate downstream signaling pathways crucial for T cell activation. CRAC channels are an attractive therapeutic target for alleviation of autoimmune diseases. Using high throughput chemical library screening targeting Orai1, we identified a novel class of small molecules that inhibit CRAC channel activity. One of these molecules, compound 5D inhibited CRAC channel activity by blocking ion permeation. When included during different… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
4
1

Citation Types

8
65
0
1

Year Published

2015
2015
2021
2021

Publication Types

Select...
7
1

Relationship

0
8

Authors

Journals

citations
Cited by 70 publications
(74 citation statements)
references
References 63 publications
8
65
0
1
Order By: Relevance
“…Inhibition of Kv1.3 depolarizes the plasma membrane and reduces the electrical gradient required for Ca 2+ influx through CRAC channels in T cells (40). More recently, Gwack and colleagues identified inhibitors of CRAC channels that prevented the development of EAE in mice when administered at the time of EAE induction (41). We show here, for the first time to our knowledge, that inhibition of CRAC channels during established EAE ameliorates CNS inflammation and disease severity.…”
Section: Discussionmentioning
confidence: 99%
See 2 more Smart Citations
“…Inhibition of Kv1.3 depolarizes the plasma membrane and reduces the electrical gradient required for Ca 2+ influx through CRAC channels in T cells (40). More recently, Gwack and colleagues identified inhibitors of CRAC channels that prevented the development of EAE in mice when administered at the time of EAE induction (41). We show here, for the first time to our knowledge, that inhibition of CRAC channels during established EAE ameliorates CNS inflammation and disease severity.…”
Section: Discussionmentioning
confidence: 99%
“…A recent study showed decreased expression of the Th17-specific transcription factors RORα and RORγt in Th17 cells from Orai1 −/− mice (41). By contrast, we did not observe reduced mRNA and protein expression of Rorc in Th17 cells and Tbx21 in Th1 cells derived from Orai1 fl/fl Cd4-Cre mice.…”
Section: Discussionmentioning
confidence: 99%
See 1 more Smart Citation
“…To date, intense drug discovery efforts have focused on developing small-molecule CRAC-channel antagonists (40)(41)(42) or specific Orai1 Abs (43) to treat autoimmune diseases and chronic inflammation. We propose using these compounds in association with RTX or, more generally, with drugs inducing a CD95-dependent apoptotic pathway, to constitute a new therapeutic opportunity for patients.…”
Section: Discussionmentioning
confidence: 99%
“…These signaling ligands regulate expression of the Alzheimer Disease related amyloid precursor protein (APP), analogous with HOMER3 (#7). Retinoic acid signaling in hippocampus is itself driven by calcium signaling (Kim et al, 2014), and regulates 4 genes: LMO1 (#6) (Rice et al, 2004); TTR (#3) (Brouillette and Quirion, 2008); AQP3 (#9) (Song et al, 2008); and shares regulation of Netrin G2 (#10) (Korecka et al, 2013) with the calcium signaling mechanism.…”
Section: Hub-and-spoke Analysismentioning
confidence: 98%